Reading anxiety and reading comprehension performance in English among EFL learners in a Malaysian university - Dialami, Shiva (2013)
This study investigated the relationship between reading anxiety and reading comprehension performance according to background variables (i.e., age, gender,discipline, and duration of the programme). The data was collected from 100 international students who enrolled in the Tertiary English Programme (TEP) at University Putra Malaysia (UPM). The participants took the Foreign Language Reading Anxiety Scale (FLRAS), the Foreign Language Classroom Anxiety Scale (FLCAS) and reading comprehension tests as pre-test and post-test. This study adopted a correlational design which employs quantitative approaches. The theoretical framework behind this research is Bernhardt‟s compensatory model of L2 reading (2000- 2005), which acknowledges the role of affective factors such as anxiety could help to clarify the existing variance in reading performance. Descriptive statistics, Pearson‟s correlation, one-way ANOVA, paired sample t-test,and independent sample t-test were employed to analyse the data. The findings revealed that there was a medium level of foreign language (FL) reading anxiety (RA) among international students. In addition, a significant negative relationship was found between the FL reading anxiety and FL reading comprehension performance scores. Thus, the high anxiety group gained lower scores on the tests than the moderate or low anxiety group and this could be attributed to the role played by debilitating anxiety. The results showed that FL reading anxiety is related to, but distinguished from, general FL anxiety. Also, there was no significant difference in their FL reading anxiety scores and reading comprehension scores among the different age groups. This means that the students‟ age have no bearing on RA. An insignificant difference was found between the two gender groups in their FLRAS scores. However, gender groups significantly differed in their reading comprehension performance with males performing only slightly better in reading comprehension. In other words, gender does play a significant role in reading comprehension but not in RA. Furthermore, none of the discipline groups (Engineering and non-Engineering) significantly differed from each other in RA and reading comprehension test;therefore, discipline did not play a key role in the participants‟ level of RA and reading comprehension performance. In addition, significant differences were found in participants‟ scores in the pre- and post-test administration of reading comprehension test and FLRAS questionnaire. Therefore, duration has an effect on both the levels of RA and reading comprehension performance of the students. Further studies to investigate the influence of reading anxiety should include other EFL learners from other universities to enable the results to be generalized to the general population and thus examine the reading comprehension performance of students in a more controlled context.